A cargo ship from Lake Onega and the shipbuilding tradition in Northern Russia - Sorokin, Petr (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In 2018, the wreckage of a sewn ship was discovered in Lake Onega near the city of Vytegra, Russia. The wreck was dated by the dendrochronological method to the mid-17th century. The wreck included a bottom (20.6 × 1.64 m) made up of five timbers, with the bases of the stems and the frames up to 5.8 m in length, as well as two fragments of the sides of the ship. The construction style of the ship is similar to the Late Medieval North Russian ship, based on three archaeological vessels. In many respects the Vytegra ship corresponds to the design of the lodia, described in documents from the 17th and 18th centuries.